Utilizing humor among teaching colleagues and its effect on their happiness in Islamic higher education of Indonesia - Fahmi Gunawan; Imelda Wahyuni (Proceedings of AICS - Social Sciences, 2017)
Humor is an essential part everyday communications and it is a fundamental facet of work relationships. Hence, humor becomes extremely significant, particularly for teaching colleagues in Indonesia during break after teaching. Humor can enhance communication, self-confidence and intimacy, reduce stress, release fatigue and tension, motivate to work and stimulate creativity. With humor, teaching colleagues can discuss how to enhance teaching skills and utilize good media in learning process. This study aimed to examine the utilization of humor among teaching colleagues in Islamic State Institute of Kendari as one of the Islamic higher educations in Indonesia. Descriptive qualitative method was utilized to analyze data in this research. Interviewing, observing, and documenting were conducted to collect data. The research results revealed that in creating humor, teaching colleagues often utilize linguistic aspects such as phonological aspects. Those phonological aspects are substitution, permutation, decreasing, and addition. Those tend to utilize adaptive humor style pioneered by Martin et al. (2003) which can elevate happiness among teaching colleagues. When they feel happy, their work performance either individually or in a group to complete certain works will be improved, as well as their work relationship, cooperation and collaboration. Finally, this research confirms that phonological aspect is one of language elements to create humor and could affect the happiness which leads the lecturers to have good interpersonal relation, cooperation and collaboration in undertaking certain jobs among teaching colleagues in Indonesia.